Enantioselective dual catalysis of N-heterocyclic carbene and hydrogen-bond donor organocatalysts - Wang, Hongling (2022)
N-heterocyclic carbene (NHC) catalysis has become a versatile catalysis strategy for building molecules via unique reaction modes. Dual catalytic processes using NHCs in combination with additional modulating agents such as another organocatalyst or transition-metal catalyst have also been studied. The clear selection of cocatalysts has led to enhanced reactivity, increased yields, and/or improved stereoselectivity. This minireview is to provide readers with a brief overview of the development and applications of NHC and hydrogen-bond donor for dual catalytic reactions.